Penyebab Turunnya Kinerja Kompresor Udara Tiga Tingkat pada saat Proses Olah Gerak di Kapal Mv. Oriental Jade - Baskoro, Lorenzo Heyting Baskoro; Prasetyo, Dwi; Utari, Riyadini (Indonesian Journal of Marine Engineering, 2025)
The performance of the three-level air compressor on the ship has an important role in supporting the motion process, especially in supporting the main engine system. This study aims to analyze the factors that cause the decline in the performance of the three-level air compressor on board MV Oriental Jade. Descriptive qualitative research methods and a fishbone diagram approach, data was obtained through direct observation, interviews with crew members, and documentation studies. The research identified four main causes of air compressor performance degradation, namely narrowing of the air passage at the air radiator due to dirt accumulation, jamming of the spring concentric valve due to over running hours and dirt, and malfunction of the unloader valve. These problems caused the air pressure in the compressor to drop to 10 bar, far below the ship's optimal requirements. The impacts included delays in maneuvering, disruption of main engine operations, and a decrease in the ship's overall efficiency. This research provides recommendations in the form of increasing the frequency of air compressor maintenance, replacing components such as spring concentric valves and unloader valves that have passed the usage time limit, and routine cleaning of radiator water. In addition, the implementation of a better monitoring system can help detect potential damage early on. The findings are expected to serve as a practical guide for ship operators and fleet managers to improve the operational efficiency of the tri-level air compressor and reduce the risk of disruption to the ship's propulsion process.